Developmental Coordination Disorder, Motor Performance, and Daily Participation in Children with Attention Deficit and Hyperactivity Disorder - Rebeca Montes-Montes; Laura Delgado-Lobete; Sara Rodríguez-Seoane (MDPI AG, 2021)
Children with Attention Deficit and Hyperactivity Disorder (ADHD) often present with Developmental Coordination Disorder (DCD) or motor coordination problems that further impact their daily functioning. However, little is known about the prevalence of co-occurring DCD and ADHD in the Spanish context, and research about the impact of ADHD on performance and participation in motor-based activities of daily living (ADL) is scarce. The aims of this study were to explore the prevalence of co-occurring DCD in children with ADHD, and to examine differences in performance and participation in motor-based ADL between children with ADHD and typically developing children. We conducted a case-control study including 20 children with ADHD and 40 typically developing controls randomly matched for exact age and sex (males = 80%; mean age = 8, 9 (2, 3) years). Presence of probable DCD (p-DCD) was confirmed with the Developmental Coordination Disorder Questionnaire (DCDQ). The DCDDaily-Q was administered to assess performance and participation in ADL. A 75% prevalence of p-DCD was found in the ADHD group (OR = 27; p < 0.001). Children with ADHD showed poorer motor performance and less participation in ADL (p < 0.01; d = 0.9-1.4). These findings contribute to understand the functional consequences of ADHD in motor-based ADL and its relationship with DCD.